Local Raw Materials and Food Quality in Shaping Local Economic Linkages: The Mediating Role of Consumer Satisfaction - Hommy Dorthy Ellyany Sinaga; Petrus Loo; Rahmad Dianta Purba; Asliza Yusoff (EKUILIBRIUM : JURNAL ILMIAH BIDANG ILMU EKONOMI, 2026)
This study investigates the role of local raw materials in improving food quality and shaping local economic linkages, using the Yoku Yatta restaurant in Medan as a case study. Based on a survey of 140 consumers and analyzed using a quantitative SEM-PLS approach, the research examines the relationships between local raw material quality, food quality, consumer satisfaction, and the local economic linkages impact. The results indicate that the use of local raw materials significantly enhances food quality and contributes to strengthening local economic linkages through supply-side interactions. Food quality is a key driver of consumer satisfaction; however, its effect on economic linkages is fully mediated by consumer satisfaction. Instead, its influence is transmitted indirectly through consumer satisfaction, which serves as a crucial mediating mechanism. This finding highlights the study’s primary theoretical contribution by demonstrating the importance of consumer satisfaction as a mechanism connecting product quality and local economic benefits. These results reflect recent trends in the Indonesian culinary sector, where consumer awareness of sustainability and local sourcing is increasing. Preliminary evidence from the Yoku Yatta consumer survey shows that local ingredient use not only enhances perceived quality but also helps build a positive restaurant image. The managerial implications emphasize the need to strengthen local supply chains, improving value-added communication strategies regarding local sourcing, and promote menu innovation based on local raw materials.